Feedback‐regulated transcriptional repression of FBXO31 by c‐Myc triggers ovarian cancer tumorigenesis. Issue 9 (12th January 2022) - Islam, Sehbanul; Dutta, Parul; Sahay, Osheen; Gopalakrishnan, Kesavaperumal; Muhury, Sushrita Roy; Parameshwar, Parinitha; Shetty, Praveenkumar; Santra, Manas Kumar
Abstract: FBXO31, a member of F‐box protein family, has been shown to play an important role in preventing tumorigenesis by preserving genomic stability during cell proliferation as well as upon genotoxic stress. Inactivation of FBXO31 due to loss of heterozygosity is associated with various cancers, including ovarian cancer, one of the deadliest forms of gynecological cancers. However, the role and regulation of FBXO31 in ovarian cancer remained elusive. Here, using biochemical and molecular biology techniques, we show that c‐Myc suppresses the mRNA levels of FBXO31 in ovarian cancer. Chromatin immunoprecipitation experiment showed that c‐Myc is recruited to the promoter region of FBXO31 and prevents FBXO31 mRNA synthesis. In contrast, FBXO31 maintains the c‐Myc expression at an optimum through proteasome pathway. FBXO31 interacts with and facilitates the polyubiquitination of c‐Myc through the SCF complex and thereby inhibits ovarian cancer growth both in vitro and in vivo. Moreover, FBXO31‐mediated proteasomal degradation of c‐Myc is unique. Unlike other negative regulators, FBXO31 recognizes c‐Myc in phosphorylation independent manner to direct its degradation. Further, expression levels analysis revealed that c‐Myc and FBXO31 share a converse correlation of expression in ovarian cancer cell lines and patient samples. We observed an increase in the expression levels of c‐Myc with a concomitant decrease in the levels of FBXO31 in higher grades of ovarian cancer patient samples. In conclusion, our study demonstrated that oncogene c‐Myc impairs the tumor‐suppressive functions of FBXO31 to promote ovarian cancer progression, and therefore c‐Myc‐FBXO31 axis can be explored to develop better cancer therapy. Abstract : What's new? Malignant potency in ovarian cancer is closely associated with the oncogenic activity of c‐Myc. In contrast, FBXO31 is known to be inactivated through loss of heterozygosity, suggesting its role as a tumour suppressor gene. However, the role and regulation of FBXO31 in ovarian cancer remain elusive. This study shows that the transcriptional inactivation of FBXO31 by c‐Myc promotes ovarian cancer malignancy. In a negative feedback loop, FBXO31 delays ovarian cancer growth through degradation of c‐Myc at the proteasomal level. The results suggest that the cross‐talk between FBXO31 and c‐Myc could potentially be exploited as a new therapeutic avenue.